Long-term management of IPF with pirfenidone – a clinical case study with 5 years follow-up - Richeldi, L.; Sgalla, G.; Cerri, S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Idiopathic pulmonary fibrosis (IPF) is a progressively fibrotic interstitial lung disease that is associated with a median survival of 2−5 years from initial diagnosis. To date, the search for an effective treatment has involved numerous clinical trials of investigational agents but without significant success. Nevertheless, research over the past 10 years has provided us with a wealth of information on its histopathology, diagnostic work-up, and a greater understanding of its pathophysiology. Specifically, IPF is no longer thought to be a predominantly pro-inflammatory disorder. Rather, the fibrosis in IPF is increasingly understood to be the result of a fibroproliferative and aberrant wound healing cascade. The development of therapeutic targets has therefore shifted in accordance with this paradigm change. Emerging clinical data from recently published and ongoing trials investigating new potential pharmacological agents should be considered in the routine clinical management of these patients. Based upon encouraging results from randomised-controlled trials showing a positive effect in slowing decline in pulmonary function and reducing disease progression, pirfenidone was approved in 2011 as the first treatment in patients with IPF. This case study describes the clinical course of a patient enrolled into the Phase III and open-label extension studies of pirfenidone.